1600 Assessing Necessity and Cost-Effectiveness of Routine Pre-Thyroidectomy Group and Save Tests. (12th October 2021) - Karim, S; Halliday, C; Shah, S; Vaughan, D
Abstract: Aim: To determine the necessity and cost effectiveness of routine blood group and save tests (G&S) before thyroidectomy Background: Sub-total or total thyroidectomy is the mainstay of treatment for several thyroid disorders. The incidence of post-thyroidectomy haemorrhage has been reported between 0.36% and 4.3% in the literature. Many patients undergo routine G&S testing in anticipation of a peri-operative haemorrhage requiring blood transfusion. Method: Retrospective review identified 276 patients undergoing an elective total or sub-total thyroidectomy at a London University Teaching Hospital between February 2018 and August 2020. Electronic medical and transfusion department records were audited to identify patients who had pre-operative G&S tests, pre-operatively reserved blood products and peri-operative transfusions. Results: 261 (94.6%) patients had a valid pre-operative group and save test. 17 (6.16%) patients had a total of 61 units of blood products ordered pre-operatively. Only 2 patients required transfusion. Conclusions: The blood transfusion rate for elective thyroidectomies at this centre was 0.72%. Routine G&S tests cost the trust thousands of pounds and create unnecessary burden on healthcare providers' time and hospital resources. We propose that routine pre-operative G&S tests are unnecessary for elective thyroidectomies.